Determinantes do desempenho educacional no Estado de Minas Gerais - Paula, Josiane Souza de (2017)
The way which education affects people s future performance is still poorly understood. literature to measure knowledge and skills. The assumption is that the results of these tests are research in this area found a high predictive value in variable related to the family. However, recent studies have also considered the importance of school-related variables. This dissertation aimed at analyzing the determinants of education performance in standardized tests of students located in the state of Minas Gerais, by means of data concerning Prova Brasil (Brazil Test) of 2013. The employed methodology was based on a hierarchical model, more indicated to deal with the hierarchical nature of educational data, for students of the 4th grade / 5th grade of elementary school, based on the grades obtained in the Mathematics tests. School environment characteristics, family characteristics, and individual factors of the students were considered as school environment are important for academic performance. We highlight the relevance of variables related to the quality of educational services, such as infrastructure offered by the school, and the presence of teachers presenting higher education in Mathematics. In addition, the mother's schooling and the level of social capital are among the factors that demonstrate the value attributed to education by the student's family. Child labor is seen as a detrimental element to academic performance, since it can reduce the positive impact of family social capital. We also sought to compare the case of Minas Gerais to the state of Ceará, given the recent evolution in educational indicators in this state. Differences in the factors that affect student performance verified. Different from Minas Gerais that has different effects in terms of the level of social capital and working conditions of students, in Ceará there is differentiation among schools concerning the performance in mathematics in terms of school delay. A hierarchical logistic model was applied in order to verify the main determinants of school delay in Minas Gerais. The results showed that there is influence of student characteristics and school factors on the probability of delay, with regional differences in this aspect. In addition, it was observed that in some schools the performance of delayed students is more harmful than in others, according to their socioeconomic level. It is expected that the results will contribute to the debate and to an agenda of public policies aimed at improving the quality of education and to reduce school inequalities.